Code Switching in English Teacher Instruction: A study of the Teacher Language in English Classroom and Its Implications for Indonesian Students Language Education - Nabilah Nur Izzah; Jamiluddin; Abdul Gani, Hastini (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
Teaching English in Indonesia is not the same as teaching English in a country where English is the native language. The teacher should make sure the students understand the explanation or instruction from the teacher. In the foreign language classroom, code switching is naturally occurring to make the teaching learning process run smoothly. Therefore, this study aimed to explain the function of code switching, students perceptions of the teacher’s code switching, and the effect of teacher’s code switching practices on students’ understanding in the teaching learning process. It was conducted at SMAN 9 Palu by using descriptive qualitative as the method. The researcher used observation, questionnaire and interview to get the data. The results of the study showed that first, there were three functions of code switching used by the teacher proposed by Sert (2005), those are topic switch, affective function, and repetitive function. Second, most of the students had positive perceptions about students' understanding and students' feelings during learning with code switching used by the teacher. Third, code switching used by the teacher in teaching learning English process provides a positive effect in providing a positive learning environment, and facilitating students with low level of second language proficiency . Keywords: Code switching, English classroom, teacher instruction